Deletion of voiced plosives in Chilean Spanish - Verdugo Maturana, Carlos (Onomázein, 2019)
The following paper is a quantitative analysis of the influence of linguistic and social factors over the deletion of the voiced plosive series /bdg/ in Chilean Spanish, in order to determine whether the deletion of the series follows the same conditioning that has been described for its weakening. The study is based on a sample of ten informants native to Santiago in sociolinguistic interviews using four speech styles. Additionally, a careful procedure of spectrographic inspections and identification of non-deleted and deleted variants of the series was defined. After the coding and analysis, it is concluded that the voiced plosive series does not present a regular behaviour in the deletion of these segments in intervocalic contexts. Deletion of voiced plosives /b/ and /d/ was found mainly in reduced speech contexts, but style of speech was not a factor for /g/ deletion. Voiced plosive /d/ showed 65.6% of deletion, in addition to showing a stronger tendency to deletion in more linguistic contexts and across genders. Voiced plosive /b/ showed 37.6% of deletion, in similar linguistic contexts as for /d/, but more predominant in male speakers. Voiced plosive /g/ showed 5.8% of deletion, and its conditioning for deletion differed from /b/ and /d/ with regards to linguistic factors, and neither gender nor speech style were seen as factors involved in its deletion.